2011
DOI: 10.3892/ol.2011.372
|View full text |Cite
|
Sign up to set email alerts
|

Elevated microRNA-126 is associated with high vascular endothelial growth factor receptor 2 expression levels and high microvessel density in colorectal cancer

Abstract: Abstract. MicroRNAs (miRNAs) are involved in a number of biological processes, including tumour biology. Pre-clinical studies have shown that miRNA-126 regulates signalling downstream of vascular endothelial growth factor receptor 2 (VEGFR-2) and, consequently, angiogenesis. The aim of this study was to analyse the possible relationship between miRNA-126, VEGFR-2 and angiogenesis in tumour tissue from patients with colorectal cancer (CRC). Tumour tissue was obtained from 81 patients. The miRNA-126 and VEGFR-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…A similar positive relationship between these two parameters has been seen in previous studies of patients with CRC [31,33], while negative correlations have been detected in other solid tumours [19,20]. Possible reasons for these divergent results are; inclusion of multiple different tumour types, disease stages, comparability of samples (non-adjacent sections as in this study), analytic methodology, ethnicity, and technical differences between quantification of immunohistochemical estimates and the PCR outcome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar positive relationship between these two parameters has been seen in previous studies of patients with CRC [31,33], while negative correlations have been detected in other solid tumours [19,20]. Possible reasons for these divergent results are; inclusion of multiple different tumour types, disease stages, comparability of samples (non-adjacent sections as in this study), analytic methodology, ethnicity, and technical differences between quantification of immunohistochemical estimates and the PCR outcome.…”
Section: Discussionsupporting
confidence: 87%
“…The study by Li et al demonstrated a similar significant relationship between high malignancy grade and low miRNA-126 expression [30], while two other studies did not identify any significant relationships [21,31]. This may be caused by rather small sample sizes (66 < N < 110) and most importantly heterogeneous samples including stage I through IV disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increased expression of miR-126 is associated with neo-angiogenesis in colorectal cancer [29], and promotes metastasis in prostate cancer [30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite of their short length, miRNAs have been confirmed to act vital important roles in various biological processes including glycometabolism (4), angiogenesis (5), cell growth (6) and movement (7).…”
Section: Introductionmentioning
confidence: 99%